KREATIVITAS BERBAHASA DALAM SASTRA ANAK INDONESIA - Dessy Wahyuni (Madah: Jurnal Bahasa dan Sastra, 2016)
Children literature, ideally, is a form of imaginatif creation in using language which is appropriate with children’s world and need. Children literature should be able to present understanding and experiences of aesthetic values (especially in using language. Therefore, children literature are really expected to have meaningful values for children. Otherwise, in fact, the value of meaningfulness for children often neglected. By implementing stylistic approach, the writing of this article to highlight ten folklore books published byPusat Bahasa that intended to children. These story books are selected randomly in order to observe creativity in using language in the opening and closing setences in the stories. This article attempts to observe the realtionship among language,creativity and children literature. The basic assumption is that improving language creativity (for children) are able to be carried out through children literature. However, by applying descriptive analysis method, the result of this article shows that the children literature users as a media to improve the creativity in using language have not reached maximal potention. The imagination world that is produced from children’s way of thinking to produce creativity in using language are necessary to be developed and to beexplored by creating children literature that are produced by using interesting syle.